Inteligentni stenski elementi - Pogačar, Kaja; Jaušovec, Marko; Pogačar, Dušan (2018)
Intelligent partition walls. The publication deals with the topic of intelligent partition walls for the needs of the contemporary co-working office spaces. The research focuses on the possibilities of rearanging the interior spaces by elements that include a larger number of functions compared to the classic walls, by adding the possibility of transforming and adapting them to spatial and user needs. In this respect, the wall is not only separating spaces, it includes acoustic, lightning, 'smart', adaptability features, etc. The book also introduces a catalogue of innovative partition walls that can be found on the market as a product or a prototype. The evaluation of intelligent partition walls is structured into three categories, namely into responsive partition walls, flexible and inflexible partition walls. The work concludes with the notion that the aspect of adaptability as such mostly contributes to the intelligence of the partition walls.
Keywords: partition walls; co-working spaces; intelligent elements; adaptability; new technologies